Revitalisasi Karakter Peserta Didik Dalam Pemikiran Kh. Hasyim Asy’ari - Sarno Hanipudin; Lastri Khasanah; Reza Maulana (QALAM: JURNAL PENDIDIKAN ISLAM, 2021)
The problelmatika that occurs in the school environment, especially with regard to students, has invited the concerns of many circles. Violence that was previously the object of the learner, is now reversed, the perpetrator is the learner himself. Not to mention religious issues, it is almost difficult to find students who try to identify themselves as 'santri' who put forward 'anggah ungguh', the portrait recorded precisely what happened is the opposite.Looking at this phenomenon, it is necessary to revitalize the character of learners from various aspects. The author sees, a lot of religious literacy that can be used as a reference, one of which is KH. Hasyim Asy'ari. This research tries to present kh thinking. Hasyim Asy'ari is contained in the books he wrote about the character of the learners